Impact of probiotics on muscle mass, muscle strength and lean mass: a systematic review and meta‐analysis of randomized controlled trials. Issue 1 (22nd November 2022) - Prokopidis, Konstantinos; Giannos, Panagiotis; Kirwan, Richard; Ispoglou, Theocharis; Galli, Francesco; Witard, Oliver C.; Triantafyllidis, Konstantinos K.; Kechagias, Konstantinos S.; Morwani‐Mangnani, Jordi; Ticinesi, Andrea; Isanejad, Masoud
Abstract: Probiotics have shown potential to counteract sarcopenia, although the extent to which they can influence domains of sarcopenia such as muscle mass and strength in humans is unclear. The aim of this systematic review and meta‐analysis was to explore the impact of probiotic supplementation on muscle mass, total lean mass and muscle strength in human adults. A literature search of randomized controlled trials (RCTs) was conducted through PubMed, Scopus, Web of Science and Cochrane Library from inception until June 2022. Eligible RCTs compared the effect of probiotic supplementation versus placebo on muscle and total lean mass and global muscle strength (composite score of all muscle strength outcomes) in adults (>18 years). To evaluate the differences between groups, a meta‐analysis was conducted using the random effects inverse‐variance model by utilizing standardized mean differences. Twenty‐four studies were included in the systematic review and meta‐analysis exploring the effects of probiotics on muscle mass, total lean mass and global muscle strength. Our main analysis ( k = 10) revealed that muscle mass was improved following probiotics compared with placebo (SMD: 0.42, 95% CI: 0.10–0.74, I 2 = 57%, P = 0.009), although no changes were revealed in relation to total lean mass ( k = 12; SMD: ‐0.03, 95% CI: −0.19 – 0.13, I 2 = 0%, P = 0.69). Interestingly, a significant increase in global muscle strength was also observed among six RCTs (SMD: 0.69, 95% CI: 0.33–1.06, I 2 = 64%, P = 0.0002). Probiotic supplementation enhances both muscle mass and global muscle strength; however, no beneficial effects were observed in total lean mass. Investigating the physiological mechanisms underpinning different ageing groups and elucidating appropriate probiotic strains for optimal gains in muscle mass and strength are warranted.